The Book of Revelation and the First Years of Nero’s Reign - Rojas-Flores, Gonzalo (2004)
In this article I try to demonstrate that the Book of Revelation was written in the first years of Nero’s reign, because (a) there is an important patristic tradition in favor of Nero and (b) the internal evidence shows that the text was redacted after Nero’s ascension to the throne in 54 and before the earthquake of Laodicea in 60.